EFEKTIVITAS SEMANGGI AIR (MARSILEA CRENATA) TERHADAP KADAR TSS PADA FITOREMEDIASI LIMBAH CAIR - Hanasari Faida Pranama; Devany England Filany, Aulia Widiawati Fitriana Dewi, Jian Tikasari, Andien Narita Putri Warisman, F (Jurnal Salome : Multidisipliner Keilmuan, 2023)
In Indonesia, the majority of small and medium enterprises do not have a good wastewater treatment system. This condition is very detrimental considering that wastewater that cannot be handled can pollute the environment. Industrial waste can be overcome by using the phytoremediation method, for example the use of water clover plants that have been planted in liquid waste can be a phytoremediator medium for the heavy metal Pb in industrial wastewater. The method used is a literature study with Indonesian language research journals in 2013-2023. An analytical research design with supporting data related to phytoremediation in water clover (Marsilea crenata) in journal searches with the help of the internet. Search keywords related to phytoremediation and water clover plants. The keyword "phytoremediation" is 2,650 journals. In a search with the keyword "Semanggi Water Plant" as many as 818 journals. The first topic is about the effective use of the water clover plant as a phytoremediation agent. The results of the study found that the Marsilea crenata plant has the potential to reduce metal levels, especially Pb. The second topic is about several types of plants that are effectively used as phytoremediation agents. There are 5 species of aquatic plants that have potential as water phytoremediation agents due to BOD agricultural waste. Phytoremediation in Semanggi Air (Marsilea crenata) has been shown to have integration and can be used to reduce TSS levels in tofu industrial wastewater. This is supported by several studies using water clover plants. Apart from using the water clover plant, this waste can also be phytoremediated using agents from water spinach, water jasmine, lotus, cat's tail (Typha latifolia), aquatic vegetation and floating aquatic plants.